Women with Silenced Voices in the Novel Stigma by Hindhi Astina: a Psychoanalysis - Dania Dwi Lestari; Anas Ahmadi (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This research was conducted to analyze the novel entitled